2022
DOI: 10.1371/journal.pntd.0010291
|View full text |Cite
|
Sign up to set email alerts
|

Finding a chink in the armor: Update, limitations, and challenges toward successful antivirals against flaviviruses

Abstract: Flaviviruses have caused large epidemics and ongoing outbreaks for centuries. They are now distributed in every continent infecting up to millions of people annually and may emerge to cause future epidemics. Some of the viruses from this group cause severe illnesses ranging from hemorrhagic to neurological manifestations. Despite decades of research, there are currently no approved antiviral drugs against flaviviruses, urging for new strategies and antiviral targets. In recent years, integrated omics data-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 152 publications
(185 reference statements)
0
14
0
Order By: Relevance
“…They have indicated that certain conditions warrant the continuous use of statins during pregnancy; however, this recommendation does not necessarily translate to fully endorsing the use of statins during pregnancy due to their safety concerns. Given that significant morbidities from ZIKV infections occur in fetuses and neonates, protecting fetuses from complications due to ZIKV infections during pregnancy and keeping them safe from the adverse effects of drugs are the goals of anti-ZIKV therapy [ 17 ]. Additionally, lipophilic statins have been associated with muscle toxicity collectively called statin-associated muscle symptoms (SAMS), which, in rare severe cases, may require drug discontinuation [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…They have indicated that certain conditions warrant the continuous use of statins during pregnancy; however, this recommendation does not necessarily translate to fully endorsing the use of statins during pregnancy due to their safety concerns. Given that significant morbidities from ZIKV infections occur in fetuses and neonates, protecting fetuses from complications due to ZIKV infections during pregnancy and keeping them safe from the adverse effects of drugs are the goals of anti-ZIKV therapy [ 17 ]. Additionally, lipophilic statins have been associated with muscle toxicity collectively called statin-associated muscle symptoms (SAMS), which, in rare severe cases, may require drug discontinuation [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, existing flavivirus vaccines are of variable efficacy, and their development has not always been straightforward, because of the complex immunological response to infection by different flaviviruses, and the presence of multiple endemic flaviviruses in tropical regions (Fischer et al, 2020; Sridhar et al, 2018). Despite more than 60 years of research, there are currently no FDA-approved antivirals to treat flavivirus infection, and there is an urgent need for these to be developed (Komarasamy et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…There are currently no approved JEV antiviral drugs despite decades of research and several compounds showing efficacy in vitro and in mouse models 29 . This is partly due to the difficulty of conducting clinical trials for JEV since outbreaks are unpredictable and occur in remote settings and recruitment is challenging due to a lack of good‐quality diagnostics.…”
mentioning
confidence: 99%
“…The JEV antiviral drug pipeline includes newly developed compounds and repurposed existing drugs, such as prochlorperazine, niclosamide, nitazoxanide and ivermectin 9,29–31 . Drug repurposing is attractive as registered drugs already have regulatory approval and their safety has been established, whereas bringing a novel tropical disease drug to market is a financial risk for pharmaceutical companies.…”
mentioning
confidence: 99%
See 1 more Smart Citation